Physiologic Responses to Dietary Sulfur Amino Acid Restriction in Mice Are Influenced by Atf4 Status and Biological Sex. Issue 4 (29th January 2021) - Jonsson, William O; Margolies, Nicholas S; Mirek, Emily T; Zhang, Qian; Linden, Melissa A; Hill, Cristal M; Link, Christopher; Bithi, Nazmin; Zalma, Brian; Levy, Jordan L; Pettit, Ashley P; Miller, Joshua W; et al.
ABSTRACT: Background: Dietary sulfur amino acid restriction (SAAR) improves body composition and metabolic health across several model organisms in part through induction of the integrated stress response (ISR). Objective: We investigate the hypothesis that activating transcription factor 4 (ATF4) acts as a converging point in the ISR during SAAR. Methods: Using liver-specific or global gene ablation strategies, in both female and male mice, we address the role of ATF4 during dietary SAAR. Results: We show that ATF4 is dispensable in the chronic induction of the hepatokine fibroblast growth factor 21 while being essential for the sustained production of endogenous hydrogen sulfide. We also affirm that biological sex, independent of ATF4 status, is a determinant of the response to dietary SAAR. Conclusions: Our results suggest that auxiliary components of the ISR, which are independent of ATF4, are critical for SAAR-mediated improvements in metabolic health in mice.